The electronic text and a new nature of literacy - Garzón Barreto, Nelly (Colombian Applied Linguistics Journal, 2006)
The electronic text has provoked a new evolution on the concept of literacy. The new features of digital text have opened new dimensions to the way literacy should be understood. The electronic text has acquired new attributes that have dramatically influenced literacy practices. Printed and digital texts share some basic features, however the digital hypertext is indeed more complex than the printed one due to that the former is usually enriched with multimedia resources. Additionally, the quality and quantity of information found in the digital text have added new reading requirements to electronic text users. Readers might need to make a more efficient use of the competencies they already manage with printed text in order to face the digital one. This paper is an attempt to understand this new literacy scenario. The discussion is devoted to exposing some features of the electronic text in order to support the idea that the concept of literacy should be as broad as to cope with the competencies and skills the features of the digital text demand. The pedagogical implications emphasize on the challenges the electronic text takes to school.